A Framework for The Design of Effective Learning Environments in the AI Era: Egyptian Students’ Preferences from Humanities versus Engineering Disciplines - Hala Assem; Wesam Morsi (JES: Journal of Engineering Sciences)
The AI revolution has increased interest in the use of digital technologies and virtual reality learning environments (VRLEs) regardless of students’ discipline and the design of these environments. This study investigates students’ preferences from Humanities vs. Engineering disciplines towards diverse learning environments (LEs) and their design to enforce the design of effective LEs that promote the productivity and wellbeing for different disciplines. The research proposes a framework that integrates AI-driven technology-enhanced learning, learning and discipline-specific theories, inaddition to architecture design for human-wellbeing theories to design effective learning environments based on an interdisciplinary research. The methodology followed a cross-sectional, quantitative, non-experimental research design with 141 undergraduates from two private universities in Egypt. Results revealed that students of both disciplines preferred Physical classrooms. Following, Engineering students preferred Mixed LEs, but Humanities students preferred VRLEs over Online Learning. Furthermore, students from both disciplines rated “lighting” as the most important architectural design element in a physical and VR LEs, to enhance their focus and feeling comfortable, however, the ratings for the other two design elements differed between students of the two disciplines. Future research can make use of the proposed framework with larger samples. It is recommended to customize the design of LEs to adapt to students’ different disciplines, learning styles and customise design elements that enhance students’ wellbeing and productivity LEs. Using